Characterization of the roles of neuropeptide-activated GPCR20 and two decarboxylases for pairing-dependent developmental processes in female Schistosoma mansoni - Li, Xuesong; Justus Liebig University Giessen (My University, 2023)
Schistosomes are parasitic flatworms that cause schistosomiasis, a NTD of worldwide importance for human and animal health. Standard treatment of schistosomiasis relies on a single drug, praziquantel (PZQ). However, several reports discussed the possibility of resistance development in Schistosoma mansoni against PZQ, and a vaccine is not yet available. Therefore, alternative treatment options are urgently needed, which requires substantial efforts in basic and applied research. Schistosomes are the only mammalian flatworms that have evolved separate sexes. Furthermore, female development in schistosomes is tightly controlled by the male partner and characterized by a high turn-over of gonadal cells in the female. This finally leads to egg production, which represents the major cause for clinical symptoms and the pathologic consequences of schistosomiasis. In this context, goal of my study was to characterize genes that are involve in the male-female interaction of schistosomes, and which may contribute to female sexual maturation. Previous omic studies have detected several genes as being significantly differentially transcribed between pairing experienced males (bM), pairing-unexperienced males (sM), pairing experienced females (bF), and pairing-unexperienced females (sF). Among these were genes involved in neuronal processes, including some G protein-coupled receptor (GPCR) genes, for which a pairing-influenced transcript occurrence was discovered with high transcript levels in bM, sM, and sF, whereas comparably low or no transcripts of these GPCRs occurred in bF. Besides their interesting roles in controlling diverse biological processes, GPCRs also represent promising targets for new anthelmintics. Although GPCRs represent a prominent receptor class in schistosomes, functional studies are limited as well as our knowledge about their ligands. Candidate ligands are neuropeptides acting as neurotransmitters, neuromodulators, or hormones in the nervous system. Transcriptomics studies in S. mansoni indicated that nearly all neuropeptide genes (Sm_npps) and a subgroup of GPCRs exhibited sex- and pairing-dependent expression profiles. Among these was the rhodopsin orphan GPCR20 (SmGPCR20), which was characterized in my study. Here, first evidence is provided for specific interactions between SmGPCR20 and two unclassified Sm_npps, Smnpp26, and Smnpp40, using bioinformatics, molecular, physiological, and biochemical approaches. According to functional analyses by RT-qPCR, Smgpcr20, Smnpp26, and Smnpp40 showed sex- and/or pairing-influenced transcript profiles. Whole-mount in situ hybridization (WISH) exhibited transcripts of these three genes in neuronal cells, sub-tegumental cells, and the parenchyma of both sexes. Transcripts of these genes co-localized in the anterior “head” region of sF and in particular patterns along the worm body indicating neuronal expression. RNA interference (RNAi) experiments with dsRNAs against these three genes resulted in reduced egg production, while pairing stability was unaffected. Furthermore, confocal microscopy (CLSM) revealed morphologic changes in the female gonads. RNAi in first-time paired females caused a reduced length of females after double RNAi against SmGPCR20 and SmNPP26, and morphological changes in the ovary. In addition, reduced transcript levels of egg formation-associated and gonad-specifically transcribed genes and the stem-cell marker nanos-1 were found. The obtained results suggest that SmNPP26 and SmNPP40 are potential ligands of SmGPCR20, and they point to a multifaceted role of SmGPCR20 in concert with SmNPP26 and SmNPP40 for the growth of first-time paired females, oogenesis, and egg-production. Therefore, the results obtained in my study contribute to the understanding of Rhodopsin-family GPCRs, their potential ligands, and their potential roles for the biology of S. mansoni. Further studies are needed to substantiate the specificity of SmNPP-GPCR20 interaction, e.g., by FRET analysis or related techniques, which will finally lead to its complete deorphanization. With respect to their druggability and the urgent need to find alternative treatment options to fight schistosomiasis, unravelling the biological function(s) of GPCRs will lead us to potential targets for the design of novel drugs - especially when receptors are in focus that exhibit a low homology to their host counterparts. Further differentially transcribed genes analyzed in my work with an expression bias towards paired males were annotated as decarboxylases (DDC or TDC), Smp_135230 and Smp_171580, enzymes involved in neurotransmitters and neuromodulator synthesis. For both genes, previous RNA-seq analyses showed significantly higher transcript levels in bM compared to sM, and no transcripts occurred in bF or sF. Results of RT-qPCR analyses with RNA from males following pairing, separation, and re-pairing in vitro supported the RNA-seq data and demonstrated an influence of pairing on the upregulation of Smddc-1 in bM. With respect to their male-specific/preferential transcript occurrence, both genes were hypothesized as male-competence factors, which were defined as gender-specifically and/or preferentially as well as pairing-dependently regulated genes transcribed in males to contribute to the induction and/or maintenance of female sexual maturation. According to sequence analyses, Smp_135230 is an L-tyrosine decarboxylase (Smtdc-1), while Smp_171580 is a DOPA decarboxylase (Smddc-1). Both genes are male-specifically/preferentially transcribed and in a pairing-dependent manner which was confirmed by RT-qPCR analyses. WISH experiments located transcripts in neuronal cells of the male´s ventral surface, the gynaecophoric canal, which faces the female during pairing. Based on improved in vitro-culture conditions for re-pairing experiments of S. mansoni in vitro, RNAi experiments against these genes resulted in reduced egg production, which was partly rescued by dopamine treatment. In addition, conclusive evidence was provided that these genes are part of the molecular communication processes between males and female during pairing, and they control ovary differentiation as part of the pairing-induced female sexual maturation.
Keywords: ddc:630